Reducing delays in the transfer of patients from psychiatric intensive care units (PICU) to acute inpatient services: a quality improvement project. (1st September 2021) - Challinor, Alexander; Lewis, Emily; Mitchell, Andrew; Williams, Debbie
Aim: To investigate the delays in the transfer of care of patients from psychiatric intensive care units (PICU) to acute care inpatient wards; Background: Few studies have focused on the characteristics of patients requiring transfer from PICU or delays in transfer of care from PICU to inpatient beds. The efficient transfer of patients from a PICU is essential to provide a dynamic service, promote patient recovery, enable safe, timely discharges and reduce stay in unnecessarily restrictive settings; Method: A 3-month prospective study was performed on two PICUs (Brooklands and Willow), investigating delays to transfer from PICUs to open wards. Days and percentage of discharges was also examined. Following collection of the initial data cycle, Brooklands implemented a 'traffic light' tool to identify delays. Following implementation, the project was repeated one year later; Results: A total of 122 patients were analysed for delays in the transfer of care from PICU to acute open wards. Brooklands PICU demonstrated a prolonged delay to transfer of patients, prompting implementation of a delayed discharge tool, the 'traffic-light' system. Brooklands PICU subsequently demonstrated a statistically significant improvement in the days to transfer; Conclusions: This quality improvement project adds to the limited research base for delays in the transfer of PICU patients and is the first study to implement a delayed discharge tool within a PICU. Further research is required on the transfer of patients from PICUs, examining barriers for these delays and the impact of this on patients within PICU.